2017
DOI: 10.1071/rdv29n1ab190
|View full text |Cite
|
Sign up to set email alerts
|

190 SexedULTRA™, A NEW METHOD OF PROCESSING SEX-SORTED BOVINE SPERM IMPROVES CONCEPTION RATES

Abstract: The gap in fertility between conventional and sex-sorted bovine sperm, known to be on the order of 10 percentage points, has never been bridged, even by increasing the number of sex-sorted sperm per inseminate. A concerted effort in the last few years has resulted in substantial changes in all stages of the sex-sorting process to develop an improved sex-sorted product called SexedULTRA™ (Sexing Technologies, Navasota, TX, USA). In vitro tests show that SexedULTRA™ maintained sperm integrity better than the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
1
2

Year Published

2018
2018
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 0 publications
0
25
1
2
Order By: Relevance
“…Moreover, SS-FRZ had a better P/AI relative to conventional (>84%) in heifers and lactating cows than found in previous studies (DeJarnette et al, 2009(DeJarnette et al, , 2010(DeJarnette et al, , 2011Chebel et al, 2010;Norman et al, 2010;Sales et al, 2011;Healy et al, 2013;Djedović et al, 2016). To our knowledge, only 2 studies have reported greater P/AI relative to conventional semen (≥90%) than the current study with frozen SS at 2 × 10 6 sperm per straw (Borchersen and Peacock, 2009;Lenz et al, 2016), and both studies were conducted using heifers only. It is important to note, however, that since the current study was conducted, Sexing Technologies Inc.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…Moreover, SS-FRZ had a better P/AI relative to conventional (>84%) in heifers and lactating cows than found in previous studies (DeJarnette et al, 2009(DeJarnette et al, , 2010(DeJarnette et al, , 2011Chebel et al, 2010;Norman et al, 2010;Sales et al, 2011;Healy et al, 2013;Djedović et al, 2016). To our knowledge, only 2 studies have reported greater P/AI relative to conventional semen (≥90%) than the current study with frozen SS at 2 × 10 6 sperm per straw (Borchersen and Peacock, 2009;Lenz et al, 2016), and both studies were conducted using heifers only. It is important to note, however, that since the current study was conducted, Sexing Technologies Inc.…”
Section: Discussioncontrasting
confidence: 55%
“…Indeed, in some studies, different bulls were used for the SS and conventional treatments (Chebel et al, 2010;Xu, 2014); in others, different ejaculates from the same bull were used (De-Jarnette et al, 2009Norman et al, 2010). A recent trial in Germany (Lenz et al, 2016) aliquotted the ejaculate for the different SS treatments (n = 4), but used different contemporaneous ejaculates for the Figure 3. Effect of bull on pregnancy per AI (P/AI; LSM ± SEM) of lactating cows across the 4 semen treatments (a) and by semen treatment (b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other research indicates that sexed sperm was associated with a lower fertility rate in comparison with unsorted sperm when an equal number of sperm were used, and suggested that a 5‐fold increase in sperm numbers is required to achieve a fertility rate comparable to that of control semen . A recent study reported that the conception rate of a branded sexed semen packaged at 4 million sperm per straw, SexedULTRA 4 M™ developed by STgenetics™, reached that of conventional semen packaged at 15 million per straw . The branded sexed semen is made using improved media during sorting .…”
Section: Consideration Of Fertility Of Sexed Semenmentioning
confidence: 99%
“…One reason is that the conception rate after the use of sexed-sperm in AI is typically 25% lower across bulls/ inseminations compared to conventional sperm 15,16 . Pregnancy rates are 60 to 80% of the conventional sperm range or higher 17,18 , especially with the use of the recently developed SexedULTRA TM technology which included increasing the number of sperm per insemination from 2 to 4 million 19,20 . However, increasing the number of sexed-sperm per insemination dose is unable to fully compensate and restore the reduced conception rate [20][21][22] .…”
mentioning
confidence: 99%